The function of the TV report on Arab satellite channels 2014 case study (Journal of the College of Basic Education, 2022)
News broadcasts in all radio and television stations depend on several structural templates, the most important of which are the news, the report, the interview, and the talk. . etc. The television report occupies a wide space within the structure of the news bulletin due to its importance in light of the Arab security, political, sports and artistic conditions.